(untitled) (Revista Tópos, 2013)
O texto conduz a uma viagem pelo centro histórico de Presidente Prudente através de desenhos de percepção dos estudantes de arquitetura. Para tanto, partimos do processo de formação da representação fotográfica de Boris Kossoy relacionando-o aos mapas mentais de Kevin Lynch. Associamos a essa percepção, os pensamentos de Vilanova Artigas (“desígnio”) e Henry Lefèbvre (“obra”) para realizar uma análise do urbano sob a perspectiva das relações lote/ rua e público/ privado. Palavras chaves: lote/rua; público/privado; Vilanova Artigas; percepção; mapas mentais. RELATIONS LOT / STREET AND PUBLIC / PRIVATE MEDIATED BY DRAWING (DESIGN) AND WORK (URBAN IMAGINARY): DOWNTOWN PRESIDENTE PRUDENTE. Abstract The text leads to a trip for the historical center of President Prudente through drawing of perception of the architecture students. We started the process of formation of the photographic representation of Boris Kossoy linked it to the mental maps of Kevin Lynch. Associate with that perception, the thoughts of Vilanova Artigas ("design") and Henry Lefèbvre ("work") to analysis of the city from the perspective of the relations between lot/street and public/private. Key words: lot/street; public/private; Vilanova Artigas; perception; mental maps.